A Systematic Review On Non-Pharmacological Approaches To Reduce Procedural Pain In Children: The Role Of Comfort Holds And Distraction - Mudhol, Basavaraj; Kumar, Yogesh (Journal of Neonatal Surgery, 2025)
In this comprehensive review, researchers looked at the effectiveness of distractions and comfort holds in easing children's anxiety and discomfort during invasive and unpleasant procedures. The review integrates data from clinical trials and recommendations to assess the efficacy, safety, and feasibility of different non-pharmacological treatments in paediatric healthcare settings. To help children relax during minor procedures, blood draws, and injections, healthcare providers commonly use comfort hold techniques and distractions, such as toys, audiovisual aids, or interactive devices. The evaluation highlights numerous approaches and tools that investigate their impacts on children's physiological responses (e.g., heart rate, cortisol levels) and psychological health (e.g., concern, terror). This review compiles research that shows how diversions and comfort work together to reduce children's experience of pain, decrease the need for pharmaceutical treatments, and promote procedural compliance. How effective these treatments are depends on factors like as age, developmental level, and the type of operation. But there's evidence to suggest that these methods, when tailored to individual needs, might make procedures more pleasant. The research goes on to say that medical professionals need to be taught these ways so that they can be properly implemented and yield the best possible results. The review highlights research gaps such as the need for uniform techniques and stronger, more comprehensive trials to confirm long-term benefits, despite the fact that comfort is valuable and distractions are widely acknowledged. The use of distractions and the promotion of comfort are both emphasised as important components of pain management strategies for children